Loss of genetic diversity and increased embryonic mortality in non‐native lizard populations - Sozos N. Michaelides; Geoffrey M. While; Natalia Zajac; Fabien Aubret; Brittny Calsbeek; Roberto Sacchi; Marco A. L. Zuffi; Tobias Uller (Molecular Ecology, 2016)
Many populations are small and isolated with limited genetic variation and high risk of mating with close relatives. Inbreeding depression is suspected to contribute to extinction of wild populations, but the historical and demographic factors that contribute to reduced population viability are often difficult to tease apart. Replicated introduction events in non‐native species can offer insights into this problem because they allow us to study how genetic variation and inbreeding depression are affected by demographic events (e.g. bottlenecks), genetic admixture and the extent and duration of isolation. Using detailed knowledge about the introduction history of 21 non‐native populations of the wall lizard Podarcis muralis in England, we show greater loss of genetic diversity (estimated from microsatellite loci) in older populations and in populations from native regions of high diversity. Loss of genetic diversity was accompanied by higher embryonic mortality in non‐native populations, suggesting that introduced populations are sufficiently inbred to jeopardize long‐term viability. However, there was no statistical correlation between population‐level genetic diversity and average embryonic mortality. Similarly, at the individual level, there was no correlation between female heterozygosity and clutch size, infertility or hatching success, or between embryo heterozygosity and mortality. We discuss these results in the context of human‐mediated introductions and how the history of introductions can play a fundamental role in influencing individual and population fitness in non‐native species.